IMPLEMENTING FLIPBOOKS FOR ENGLISH LANGUAGE LEARNING AT THE ELEMENTARY LEVEL - Putri, Silviana Bilqis Setiawan; Lindawati , Rini; Ganinda, Nurhayati (Primary Education Journals (Jurnal Ke-SD-An), 2025)
This is a study that discussed the implementation of Flipbooks in English learning in elementary schools. The purpose of this study is to describe the implementation of flipbooks in English learning at the elementary level, as well as to determine students' responses to using flipbooks in learning. The research method used was qualitative research, and the subjects is grade VI students at SDN Wangkal. The results of the study show that the implementation of Flipbook in classroom learning can be described as teachers teaching in class using Flipbook media and explaining the subject material inside the Flipbook using the lecture method, while students listen and pay attention to the material in the Flipbook. The results of the study on the application of Flipbook media in learning are divided into several stages. It begins with introducing Flipbook media to students before learning begins, conducting warm-up activities, explaining the material using Flipbook media, opening videos from the Flipbook, accessing the quizizz link in Flipbook and finally students summarize/conclude the material and activities that have been learned. The response of students when using Flipbook from the cognitive aspect was agreed by the students that Flipbook really helps them in understanding and memorizing learning materials. In the motivational aspect, students also feel more motivated in learning when using Flipbook. In the affective aspect, students also agree that the appearance of Flipbook makes the learning process more enjoyable.